Feeding characteristics and growth among children with prenatal exposure to Zika virus with and without microcephaly in the microcephaly epidemic research group pediatric cohort - Danielle Maria da Silva Oliveira; Demócrito de Barros Miranda-Filho; Ricardo Arraes de Alencar Ximenes; Ulisses Ramos Montarroyos; Elizabeth B. Brickley; Maria Helena Teixeira Pinto; Celina Maria Turchi Martelli; Regina Coeli Ramos; Thalia Velho Barreto de Araújo; Sophie Helena Eickmann; Paula Fabiana Sobral da Silva; Maria Durce Costa Gomes Carvalho; et al. (BMC, 2024)
Abstract Objective To describe the feeding characteristics and growth of children with prenatal exposure to Zika virus (ZIKV) from birth to 48 months. Design Using data from the prospective Microcephaly Epidemic Research Group Pediatric Cohort (MERG-PC), children without microcephaly born to mothers with evidence of ZIKV infection during pregnancy (ZIKV-exposed children without microcephaly) and children with Zika-related microcephaly were compared using repeated cross-sectional analyses within the following age strata: birth; 1 to 12; 13 to 24; 25 to 36; and 37 to 48 months. The groups were compared in relation to prematurity, birth weight, breastfeeding, alternative feeding routes, dysphagia and anthropometric profiles based on the World Health Organization Anthro z-scores (weight-length/height, weight-age, length/height-age and BMI-age). Results The first assessment included 248 children, 77 (31.05%) with microcephaly and 171 (68.95%) without microcephaly. The final assessment was performed on 86 children. Prematurity was 2.35 times higher and low birth weight was 3.49 times higher in children with microcephaly. The frequency of breastfeeding was high (> 80%) in both groups. On discharge from the maternity hospital, the frequency of children requiring alternative feeding route in both groups was less than 5%. After 12 months of age, children with microcephaly required alternative feeding route more often than children without microcephaly. In children with microcephaly, the z-score of all growth indicators was lower than in children without microcephaly. Conclusions Children with Zika-related microcephaly were more frequently premature and low birth weight and remained with nutritional parameters, i.e., weight-for-age, weight-for-length/height and length/height-for-age below those of the children without microcephaly.